Beneficial Effects of Slow-Release Large Neutral Amino Acids after a Phenylalanine Oral Load in Patients with Phenylketonuria - Iris Scala (MDPI AG, 2021)
The mainstay of phenylketonuria treatment is a low protein diet, supplemented with phenylalanine (Phe)-free protein substitutes and micronutrients. Adhering to this diet is challenging, and even patients with good metabolic control who follow the dietary prescriptions in everyday life ignore the recommendations occasionally. The present study explores the ability of slow-release large neutral amino acids (srLNAAs) to prevent Phe increase following a Phe dietary load. Fourteen phenylketonuric patients aged ≥13 years were enrolled in a 6-week protocol. Oral acute Phe loads of 250 and 500 mg were added to the evening meal together with srLNAAs (0.5 gr/kg). Phe and tyrosine were dosed before dinner, 2h-after dinner, and after the overnight fast. After oral Phe loads, mean plasma Phe remained stable and below 600 µmol/L. No Phe peaks were registered. Tyrosine levels significantly increased, and Phe/Tyrosine ratio decreased. No adverse events were registered. In conclusion, a single oral administration of srLNAAs at the dose of 0.5 gr/kg is effective in maintaining stable plasma Phe during acute oral loads with Phe-containing food and may be added to the dietetic scheme in situations in which patients with generally good adherence to diet foresee a higher than prescribed Phe intake due to their commitments.